Obstacles In Securing Halal Certification In Malaysia: A Study On Home-Based Business (HBB) - Arif, Sazelin; Abu Bakar, Nurdinah; Mat, Zawiah; Sulaiman, Nooraini; Abdullah, Nurlisa Loke (Walailak University, 2021)
This paper aims to identify the obstacles faced by Home-Based Business (HBB) Food and Beverage (F&B) entrepreneurs in securing halal certification in Malaysia. An interview was conducted with 10 HBB entrepreneurs who run F&B businesses in the region of Melaka Tengah. This study adopts a non-probability sampling approach via snowball sampling. Snowball sampling was used so that research participants could recommend more suitable participants to be interviewed based on a few criteria set in the preliminary study. The majority of the respondents shared the same opinion that there are five (5) obstacles that prevent them from securing the Malaysian Halal Certification. The obstacles include lack of capital, failure to understand the halal requirement, stringent procedures, lack of support and guidance, as well as misconception about obtaining halal certification. These obstacles were derived from the transcribed data, which was coded and grouped according to themes. The themes were derived from the highlights of previous studies that were relevant to the research question. The identification of these obstacles has its purpose in making it easier for HBB entrepreneurs to obtain the Malaysian Halal Certification for the F&B category. The study also found that the Halal Certification Body can provide the best mechanism to make it more accessible to apply for halal certification as well as to provide manageable procedures to obtain halal certification, particularly for HBB entrepreneurs in order to enable them to compete aggressively in the global market.